Tuning photochemical properties of phosphorus(v) porphyrin photosensitizers. Issue 71 (22nd August 2017) - Meshkov, Ivan N.; Bulach, Véronique; Gorbunova, Yulia G.; Gostev, Fedor E.; Nadtochenko, Victor A.; Tsivadze, Aslan Yu.; Hosseini, Mir Wais
Abstract : Depending on the nature of axial ligands on P(v ) porphyrins, singlet oxygen generation and charge transfer processes may be tuned. Abstract : Photosensitizing and emission properties of P(v ) porphyrins were studied. The nature of the axial ligands, occupying the apical position on the P centre adopting an octahedral coordination geometry, strongly influences singlet oxygen generation and charge transfer and allows switching between the two processes.